Factors behind moral distress among Iranian emergency medical services staff: A qualitative study into their experiences - Mojtaba Jafari; Mohammadali Hosseini; Sadat Seyed Bagher Maddah; Hamidreza Khankeh; Abbas Ebadi (Kashan University of Medical Sciences, 2019)
Background: The unique characteristics of each emergency situation and the necessity to make prompt decisions cause emergency medical services (EMS) staff's ethical conflicts and moral distress. Objectives: This study aimed to explore EMS staff's experiences of the factors behind their moral distress. Methods: This qualitative study was conducted on 14 EMS staff using the conventional content analysis. Data were collected through unstructured and semi-structured interviews. Each interview was started using general questions about moral issues at workplace and barriers to professional practice. The five-step content analysis approach proposed by Graneheim and Lundman was used for data analysis. Results: The factors behind EMS staff's moral distress were categorized into 13 subcategories and 5 main categories. The main categories were staff's lack of knowledge and competence, inability to adhere to EMS protocols, restraints on care provision, ineffective interprofessional communications, and conflicts in value systems. The subcategories were, respectively, inadequate knowledge and experience, working with incompetent colleagues, artificial services, working in unpredictable situations, lay people's interference in care provision, resource and equipment shortages, barriers to early arrival at the scene, obligatory obedience to the system, poor interprofessional interactions, inadequate interprofessional trust, refusal of care, challenges in obtaining consent, and challenges in telling the truth. Conclusion: EMS staff experience moral distress at work due to a wide range of factors. Given the negative effects of moral distress on EMS staff's physical and mental health and the quality of their care services, strategies are needed to prevent or reduce it through managing its contributing factors.